Primary multiple synchronous tumors: soft tissue sarcoma of the retroperitoneal space and metastatic prostate cancer - O. A. Mailyan; K. Yu. Kanukoev; P. G. Berezin; K. M. Nyushko; V. A. Gorbach (Исследования и практика в медицине)
At the present time primary-multiple malignancies are of interest in connection with the frequency of prevalence, which remains at the rather high level and continues to grow up, therefore increasing the relevance of this pathology in clinical oncology and everyday practice. With the exception of the treatment of primary multiple malignancies requiring a multimodal approach, as well as in the case of the use of complex treatment in conjunction with chemotherapists and radiotherapy specialists. In the past three decades, the development of screening tests that prevent and detect some cancers at an early, more treatable stage, and treatment advances have increased the 5‑year relative survival rate for all cancers to 66%. In addition to concerns about cancer recurrence, survivors also worry about their risk of developing a new cancer. Prostate cancer is a leader in terms of morbidity and mortality in the world, just as often are found in combination with other malignant tumors. However, given the high detectability of prostate cancer, primary patients are currently receiving radical treatment, and if metastatic prostate cancer is detected, they are receiving drug treatment, which improves the survival and quality of life of patients. Soft tissue sarcomas are rare malignant tumors that develop in the connective tissues and remain poorly understood due to the fact that they make up less than 1% of all malignant diseases. One of the main methods for treating soft tissue sarcomas is the surgical method. Soft tissue sarcomas are difficult to treat and therefore it is imperative that surgeons and other specialists have experience in treating this disease. Studies show that patients with this pathology show better results if they receive treatment in specialized cancer centers that have experience in treating soft tissue sarcoma. This article demonstrates the clinical case of surgical treatment of a patient with primary multiple retroperitoneal tumors and metastatic prostate cancer.